2011
DOI: 10.1111/j.1744-7402.2010.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size-Dependent Hardness of Transparent Magnesium Aluminate Spinel

Abstract: Most different transparent grades of sintered and single crystalline spinel were investigated by Vickers and Knoop tests with loads of 1 kg (HK1, HV1) and of 10 kg (HV10). The hardness ranking of all samples was HK1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 12 publications
5
51
0
2
Order By: Relevance
“…These temperatures are far below the melting temperature of 3CaOÁAl 2 O 3 (1540°C) but close to that of CaOÁAl 2 O 3 (1390°C) and enabled the formation of dense (=transparent) sub-lm microstructures with high Vickers hardness HV10 (measured at 10 kgf testing load) close to 15 GPa [23,21]. -However, in common visual inspection these tiles are not completely free of larger visible defects (Fig.…”
Section: Improved Sintering By Doping Additivesmentioning
confidence: 94%
See 2 more Smart Citations
“…These temperatures are far below the melting temperature of 3CaOÁAl 2 O 3 (1540°C) but close to that of CaOÁAl 2 O 3 (1390°C) and enabled the formation of dense (=transparent) sub-lm microstructures with high Vickers hardness HV10 (measured at 10 kgf testing load) close to 15 GPa [23,21]. -However, in common visual inspection these tiles are not completely free of larger visible defects (Fig.…”
Section: Improved Sintering By Doping Additivesmentioning
confidence: 94%
“…Optical loss factor (in-line, $600 nm) =In-line transmission ($600 nm, 4 mm thickness) a For comparison: Dn = 0.5-0.9 was published as a typical value of single crystalline sapphire for lasers [21]. make use of their special refractive and dispersive properties [9] instead of addressing a ''simple'' transparency like that of security windows.…”
Section: Technical Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the sintered densities of the three ZAÀCBS samples are identical, the main factors affecting their hardness may be grain sizes and crystalline phases formed in the glass-ceramic matrix. According to A. Krell et al the impact of grain sizes that are in the range of a few microns is minor with respect to hardness, while the hardness increases as grain sizes of a sintered body decrease [29]. The grain sizes of the three ZAeCBS samples are within the range of a few microns; therefore, the indentation hardness of the ZAeCBSÀ1.2 sample (sintered at 925 C) is slightly larger than that of the ZAeCBSÀ2.9 and ZAeCBSÀ4.8 samples due to its smallest grain sizes.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…A. Krell et al reported the fabrication of spinel transparent ceramic with gelcasting method by using the nano-particle size of spinel powder as the raw materials. High transparency spinel ceramics with fine microstructures can be fabricated by this method successfully [14,15]. The aim of M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%